Profile of initial and established entrepreneurship and its motivations (Research, Society and Development, 2021)
A present study aimed to analyze the profile of entrepreneurship in the initial and established stages and its main initial motivations. The qualitative methodology, which was characterized by data from the Global Entrepreneurship Monitor (GEM 2019). The results show that in the initial stage there is a minimal difference regarding genders; more active people have characteristics such as age (between 25 and 44 years), education (complete higher education) and income (above six minimum wages); and the main motivation is financial and work independence. While in the established stage the male gender stands out; people with incomplete elementary education, aged between 45 and 54 years and income above six minimum wages are the most active; and the main motivation is to make a difference in the world.